Peace Begins with Knowledge: The Transformative Power of Education in Conflict-Affected Societies - Dr. Najma Begum (Journal of Religion and Society, 2026)
The present study undertakes a critical examination pertaining to the transformative potential of education as a tool for peacebuilding in conflict-affected societies. The primary focus of the attention is on the capacity of educational systems to foster social cohesion, reconciliation, and sustainable peace. The study in the context challenges the narrow conceptualization of education as mere skills transmission. It has moreover attempted to address a central paradox observed in contemporary discourse. This paradox relates to the coexistence of education's recognized potential for peacebuilding and its persistent underfunding and marginalization in humanitarian responses. The study in the context undertakes a systematic assessment of theoretical frameworks and empirical evidence. The analysis therefore is grounded in foundational peace theory and contemporary research. The synthesized framework helps locate education's dual capacity. It can either reinforce existing inequalities or serve as a catalyst for social transformation. The study finding reveals significant empirical evidence supporting education's peacebuilding role. Research indicates that raising primary education enrollment alone could reduce the risk of conflict by nearly seventy-five per cent. Furthermore, peace education programs demonstrate measurable impacts. Seventy-eight per cent of participants report improved conflict resolution skills and eighty-one per cent report positive behavioral changes. However, the analysis also notes persistent challenges. These include underfunding resource constraints and the need for context sensitive approaches. Therefore, the article proposes a strategic framework for integrating peacebuilding into educational systems. This framework emphasizes community led approaches trauma informed pedagogy and the meaningful participation of young people as active peacebuilders. Ultimately education must be recognized as a fundamental investment in peace not merely a humanitarian afterthought. Keywords: Peace Education Peacebuilding Social Cohesion Conflict Transformation Education in Emergencies Positive Peace Restorative Practices